2016
DOI: 10.1038/srep22670
|View full text |Cite
|
Sign up to set email alerts
|

In-situ Observation of Cross-Sectional Microstructural Changes and Stress Distributions in Fracturing TiN Thin Film during Nanoindentation

Abstract: Load-displacement curves measured during indentation experiments on thin films depend on non-homogeneous intrinsic film microstructure and residual stress gradients as well as on their changes during indenter penetration into the material. To date, microstructural changes and local stress concentrations resulting in plastic deformation and fracture were quantified exclusively using numerical models which suffer from poor knowledge of size dependent material properties and the unknown intrinsic gradients. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…This approach is comparable to the analysis done by Zeilinger et al [10] for the determination of loading stress during the fracturing of thin films. The strain state was then recalculated with the X-ray elastic constants 1 2 S 2 = 5.81 × 10 −5 MPa −1 , which are connected to the elastic modulus E and the Poisson value ν, as given by Noyan for steel specimens [9], to determine the σ xx , σ yy , σ yz , and σ zz stress components as well as the hydrostatic σ h and equivalent (von Mises) stress σ eq , as used by Kuznetsov et al [11] for the description of burnishing processes using Equation (2).…”
Section: Stress Distribution During Deep Rollingsupporting
confidence: 68%
“…This approach is comparable to the analysis done by Zeilinger et al [10] for the determination of loading stress during the fracturing of thin films. The strain state was then recalculated with the X-ray elastic constants 1 2 S 2 = 5.81 × 10 −5 MPa −1 , which are connected to the elastic modulus E and the Poisson value ν, as given by Noyan for steel specimens [9], to determine the σ xx , σ yy , σ yz , and σ zz stress components as well as the hydrostatic σ h and equivalent (von Mises) stress σ eq , as used by Kuznetsov et al [11] for the description of burnishing processes using Equation (2).…”
Section: Stress Distribution During Deep Rollingsupporting
confidence: 68%
“…Given the similarities of those cracks to the bottom median vent, one may hypothesize they are being formed during loading by grain shearing at the high stress regions, causing intergranular microcracking. Zeilinger et al 40 have shown that in ceramics, the subsurface underneath the indenter edge shows indeed a high stress gradient, which could be accommodated by grain boundary fracturing.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoindentation is the standard and most frequent method used to characterize mechanical properties of thin film materials [30]. Accordingly, studies on deformation mechanisms of thin films variants of transition-metals carbides/nitrides (TMC/N) were mainly performed through micro/nano-indentation experiments combined with modeling [31][32][33][34][35][36]. Intergranular shear sliding is identified as a common and important failure mechanism in these studies.…”
Section: Accepted Manuscriptmentioning
confidence: 99%